2008
DOI: 10.1088/1468-6996/9/4/044208
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity in transparent zinc-doped In2O3films having low carrier density

Abstract: Thin polycrystalline zinc-doped indium oxide (In 2 O 3 -ZnO) films were prepared by post-annealing amorphous films with various weight concentrations x of ZnO in the range 0 x 0.06. We have studied the dependences of the resistivity ρ and Hall coefficient on temperature T and magnetic field H in the range 0.5 T 300 K, H 6 Tfor 350 nm films annealed in air. Films with 0 x 0.03 show the superconducting resistive transition. The transition temperature T c is below 3.3 K and the carrier density n is about 10 25 -1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…8) and up to 3 K when combined with ZnO. 9 Further, Mori 10 reported a sharp SC transition in post-oxidized ITO films, with T c in the range 2-4 K. These results suggest that T c can be enhanced by increasing the carrier density via chemical doping. Fig.…”
mentioning
confidence: 94%
“…8) and up to 3 K when combined with ZnO. 9 Further, Mori 10 reported a sharp SC transition in post-oxidized ITO films, with T c in the range 2-4 K. These results suggest that T c can be enhanced by increasing the carrier density via chemical doping. Fig.…”
mentioning
confidence: 94%
“…The SEM images revealed that the grains of as-deposited and annealed films are spherical in shape and are uniformly distributed over the entire film surface [60]. The size of the grain increases with increase of annealing temperature might be due to the increase in mobility of atoms [17,61]. In addition to that, increase in annealing temperature leads to decrease in surface roughness and grain boundaries, resulted in smoothens of the film increases.…”
Section: Morphological and Elemental Studymentioning
confidence: 99%
“…In a similar fashion, highly-doped InN and In 2 O 3 show the same T as metallic In. However, the H 2 values are very much different, and thus it was assumed that superconductivity in InN [62] and In 2 O 3 [63] is genuine. The latter conclusion has been questioned recently.…”
Section: Iii-v and Iv-vi Semiconductorsmentioning
confidence: 99%